Building Employee Performance: The Synergistic Effect of Organizational Culture, Leadership Style and Organizational Commitment (International Journal of Scientific Research and Management (IJSRM), 2024)
This study examines four variables, namely organizational culture, leadership style, organizational commitment, and employee performance. The purpose of this study is to analyze and explain the influence of organizational culture, and leadership style on employee performance with organizational commitment as a mediating variable. The respondents of the study were all employees of PT. PLN (Persero) UP3 Merauke, ULP Kuprik, Merauke, Indonesia. The research sample was 41 employees with a sample collection method using the census method. The analysis techniques used are descriptive and Structural Equation Modeling which is solved by linear regression techniques. A quantitative approach was chosen to explain the influence between research variables. Data collection using questionnaires. The results of this study found that organizational culture and leadership style can influence work commitment which ultimately has a positive impact on employee performance. This means that if an organization’s organizational commitment is increased it will result in more optimal employee performance, supported by strong organizational commitment generated by a strong organizational culture and leadership style.